FAKTOR-FAKTOR PEMBENTUK MOTIVASI INTRINSIK PEKERJA PADA USAHA RESORT & SPA XYZ DI MANADO - Yuniarto, Yustinus; Moningka, Elisia Theresia Sonia (Jurnal Pengabdian dan Kewirausahaan, 2020)
Business in the Resort & Spa business sector is growing rapidly. This increase in business in the hospitality sector reflects the demand for both local and out-of-town visitors. Visitor satisfaction is an important aspect of this service industry. Several studies also focus on the relationship between satisfaction and the behavior of workers in an accommodation. This is important because service delivery according to quality standards is also determined by the performance of the workers in it. This study aims to analyse the factors that influence Intrinsic Motivation. The research subjects in this study were the XYZ company in Manado which was engaged in Resort & Spa services and the objects in this study were 92 employees who worked at the company. This study uses Partial Least Square (PLS) with SMART PLS 3.0. Intrinsic Motivation variable is not influenced by employee expectations, then this study explains that employee expectations are influenced by work boredom. Furthermore, Intrinsic Motivation is influenced by Work Boredom.